Construction of Stable Helical Metal‐Organic Frameworks with a Conformationally Rigid "Concave Ligand". Issue 42 (22nd June 2021) - Zhao, Kai; He, Ying; Shan, Chuan; Wojtas, Lukasz; Ren, Junyu; Yan, Yu; Shi, Hanzhong; Wang, Haonan; Song, Zhiguang; Shi, Xiaodong
Abstract: A helical metal‐organic framework was prepared by using a conformationally rigid tetratopic benzoic acid ligand with binding units pointing toward each other (concave ligand). To avoid the obvious intramolecular interactions between binding units, matching spacing groups were applied to introduce atropic repulsion, thereby allowing the formation of extended frameworks for the first time. With this new ligand design, a helical‐shaped MOF with significantly improved air and moisture stability was successfully prepared, thus providing a new strategy for ligand design toward porous material constructions. Abstract : Concave concept : A helical metal–organic framework was prepared by using conformationally rigid tetratopic benzoic acid ligands with binding units pointing toward each other. To avoid intramolecular interactions between binding units, matching spacing groups were applied to introduce atropic repulsion, thus forming extended frameworks. With this new ligand design, a helical MOF with significantly improved air and moisture stability was prepared, thereby providing a new strategy for ligand design for the construction of porous materials.